MVVM survival guide for enterprise architectures in Silverlight and WPF : eliminate unnecessary code by taking advantage of the MVVM pattern, less code, fewer bugs /: eliminate unnecessary code by taking advantage of the MVVM pattern, less code, fewer bugs. (2012) - Unknown
No abstract available